2017
DOI: 10.7448/ias.20.7.21753
|View full text |Cite
|
Sign up to set email alerts
|

Misdiagnosis of HIV infection during a South African community‐based survey: implications for rapid HIV testing

Abstract: Introduction: We describe the overall accuracy and performance of a serial rapid HIV testing algorithm used in community-based HIV testing in the context of a population-based household survey conducted in two sub-districts of uMgungundlovu district, KwaZulu-Natal, South Africa, against reference fourth-generation HIV-1/2 antibody and p24 antigen combination immunoassays. We discuss implications of the findings on rapid HIV testing programmes. Methods: Cross-sectional design: Following enrolment into the surve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
48
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(49 citation statements)
references
References 26 publications
(30 reference statements)
1
48
0
Order By: Relevance
“…Most studies were carried out in Africa ( n  = 48) [5,7,1014,16,2225,29,30,3234,36,37,39,41,43,44,46,47,49,51,52,54–59,61–65,67–72,74,75], followed by in the Americas ( n  = 7) [28,31,42,50,53,60,66], Asia ( n  = 4) [8,35,45,73] and Europe ( n  = 1) [48]. There were also four multi-country/regional studies [26,27,38,40].…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Most studies were carried out in Africa ( n  = 48) [5,7,1014,16,2225,29,30,3234,36,37,39,41,43,44,46,47,49,51,52,54–59,61–65,67–72,74,75], followed by in the Americas ( n  = 7) [28,31,42,50,53,60,66], Asia ( n  = 4) [8,35,45,73] and Europe ( n  = 1) [48]. There were also four multi-country/regional studies [26,27,38,40].…”
Section: Resultsmentioning
confidence: 99%
“…Nine studies reported more than one unit of measure, and three studies did not specify sample size (see supplementary information). The majority of studies occurred in a facility-based setting; studies carried out in community settings included the workplace ( n  = 1) [57], home-based testing ( n  = 2) [14,39] and a mobile setting ( n  = 1) [32]. …”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations